Estudo geomorfológico e a análise dos processos de erosão mecânica na bacia hidrográfica do Rio Tenente Amaral – MT - Jesuz, Cleberson Ribeiro de (2014)
The relationships between geomorphological features and processes of mechanical erosion in Depressão Interplanáltica Rondonópolis and Planalto dos Guimarães morphostructure present in the Tenente Amaral Watershed River (TAWR), based mostly in the municipality of Jaciara, Southern State of Mato Grosso, show interrelations very characteristic regions of the headwaters of the upper São Lourenço. In this sense the present study adheres to understand the events of mechanical erosion - laminar and gullies - in that watershed, analyzing intrinsic to these events geomorphological processes and mapping their occurrence, in order to understand the sources of sediment to the main river. The geomorphological map of the TAWR was developed from crossing and systematic analysis of clinographic maps and hypsometric area by GIS tools (ESRI ArcGIS 9.3). The processes of mechanical erosion (hydric and gullies) were mapped and presented cartographically, as well as examined in situ, and validated with the installation of 06 experimental stations, the method of erosion plots, Gerlach rain gutter in areas of distinct use of land - extensive cattle ranching and mechanized agriculture. The geomorphological mapping showed the spatial distribution of geomorphological features in the form of: Erosive scarps, colluvial deposits, exhumed surfaces, hills and valleys in Testimonials morfoescultura Depressão Interplanáltica Rondonópolis. While in morfoescultura Planalto dos Guimarães were mapped areas with occurrences of surface erosion on agricultural environment and through primary and / or secondary native vegetation, like, 39 gullies. Dealing with the processes of mechanical erosion, Rondonópolis Depression morphostructure preferably presents erosions arising from physical processes, through falling rocks (cliffs). However, in Planalto dos Guimarães morphostructure, we have actions of physico-chemical, biological and social processes, including gully process located in the headwater portions of watercourses, especially in areas that promote surface erosion loss of soil estimated average of 1,82 t / ha / day or 665 t / ha / year in the area with extensive livestock use, and 1,25 t / ha / day or 499 t / ha / year in agricultural use, uses which together represent over 78% of all TAWR area.